Muscle endurance, strength, and active range of motion in patients with different subphenotypes in systemic sclerosis: a cross-sectional cohort study. (4th March 2019) - Pettersson, H; Boström, C; Bringby, F; Walle-Hansen, R; Jacobsson, LTH; Svenungsson, E; Nordin, A; Alexanderson, H
Abstract : Objective : Proximal muscle weakness is common in patients with systemic sclerosis (SSc). Dynamic muscle endurance, muscle strength in the lower extremities, and active range of motion (AROM) in the upper extremities are less studied. We investigated functional muscle endurance, strength, and AROM, and explored differences depending on skin and/or lung involvement in SSc patients. Method : The study divided 205 patients with limited/diffuse cutaneous systemic sclerosis (lcSSc/dcSSc) into no–mild and moderate–end-stage lung involvement, the latter based on the Medsger disease severity score. Dynamic muscle endurance in shoulder and hip flexion was assessed by the Functional Index-2, lower extremity muscle strength by the Timed-Stands Test (TST), and shoulder–arm AROM by the Functional Shoulder Assessment (FSA). Results : Shoulder and hip flexion muscle endurance were reduced in relation to reference values median (IQR) [53% (27–100%) and 40% (23–90%), respectively, p < 0.001]. Patients with moderate–end-stage lung involvement had less endurance in shoulder [39% (21–71%) and hip flexion 35% (20–70%)] than patients with no-mild lung involvement [57% (33–99%) and 48% (28–100%), p < 0.05]. All patients, regardless of subtype/grouping, needed longer to complete the TST [21 s (17–27 s)] compared to reference values [17 s (15–18 s), p < 0.001], and patients with moderate-end-stage lung involvement had worse TST score than patients with no-mild lung involvement, [25 s (18–30 s) vs 19 s (16–25 s), p < 0.001]. The FSA sum scores were lower compared with reference values (p < 0.01). DcSSc patients had a lower FSA-sum score [53 (48–57)] than lcSSc patients [57 (52–60), p < 0.01]. Conclusion : SSc patients have markedly reduced muscle endurance in the upper and lower extremities, reduced muscle strength in the lower extremities, and impaired AROM in the shoulders and arms. Patients with moderate–end-stage lung involvement had more impaired muscle endurance and strength but no differences were found between lcSSc and dcSSc patients. Not only muscle strength, but also dynamic muscle endurance should be measured in SSc patients.